Calle 13: Reggaeton, Politics, and Protest - Melinda S. Molina (Washington University Journal of Law & Policy, 2015)
This Article focuses on Calle 13, a musical duo from Puerto Rico, and examines that duo’s use of social commentary and satire to confront the negative representations of Latinos, which are often used to engender support for discriminatory laws. The Article also focuses on citizenship-based voting purges because voting on a particular issue or for a candidate or party expresses some facet of the voter’s beliefs, values, and ideology. The inability to vote renders a person voiceless, relegating them to the societal periphery. The Article concludes that, through music, many voiceless communities who would otherwise be silenced by discriminatory laws and policies find their voice.
Keywords: Melinda Molina; Calle 13; voting discrimination; voting/voter disenfranchisement; music; reggaeton